2020
DOI: 10.3846/tede.2020.13970
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Retail Customers Hesitate for Shopping Grocery Online?

Abstract: Considering a relatively slow adoption of online grocery shopping in the vast majority of the world markets, the main objective of this study was to uncover any new reasons why customers hesitate to shop groceries online. Moreover, we were not looking for undiscovered discouraging reasons only but also intended to validate previously researched reasons in published studies. Thus, we have first used a systematic literature review to cover all relevant previous studies on online grocery non-buyers. Even though t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 37 publications
(54 reference statements)
1
16
0
Order By: Relevance
“…With a predicted annual growth rate of 6.7%, sales are projected to increase from $421.9 million in 2020 to $546.7 million in 2024 [3] (forecasts are adjusted for the expected impact of COVID-19). However, the uptake of online shopping proves to be highly product specific [4,5]. Whereas, worldwide, the share of online sales of consumer electronics and household appliances is expected to grow to, respectively, 39% and 31% by 2023, for food the projection is a mere 3% [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With a predicted annual growth rate of 6.7%, sales are projected to increase from $421.9 million in 2020 to $546.7 million in 2024 [3] (forecasts are adjusted for the expected impact of COVID-19). However, the uptake of online shopping proves to be highly product specific [4,5]. Whereas, worldwide, the share of online sales of consumer electronics and household appliances is expected to grow to, respectively, 39% and 31% by 2023, for food the projection is a mere 3% [6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the EU28 only 17% of individuals bought food and groceries via the Internet in 2019, compared to 41% for clothes and sport goods [7]. Overall, the current adoption rates indicate that online grocery shopping has so far been more of an evolution than a revolution [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived relative advantage refers to the degree to which using a new technology is regarded as being better than using its precursor (Venkatesh et al, 2003) thus, in this context, perceived relative advantage reflects the benefits that consumers receive by using their preferred payment method. Prior studies have observed that perceived relative advantage has a significant impact on consumers' continuance intention (Nel and Heyns, 2017;Klepek and Bauerov a, 2020). Ameen and Willis (2018) identified that perceived relative advantage has a positive impact on consumers continuance intention of mobile payments.…”
Section: Factors Affecting Consumers' Payment Preferencementioning
confidence: 97%
“…Identifying differences between users and non-users can underscore cognitive and affective responses suitable for mobile grocery app use. For instance, non-adopters of mobile grocery shopping prefer offline shopping because they can (a) see groceries in person, (b) derive pleasure from the in-person experience, and (c) save time for purchase [99]. These reasons may be reflected utilitarian, hedonic, and experiential motives in both offline and mobile grocery shopping experiences.…”
Section: Hypothesis 9 (H9)mentioning
confidence: 99%